TINJAUAN LITERATUR: AKTIVITAS ANTIDIABETES MELLITUS BEBERAPA TANAMAN FAMILI MALVACEAE - Asman Sadino; Doni Anshar Nuari; Riza Apriani; Ceceng Fajar Muharam (Jurnal Buana Farma, 2026)
The Malvaceae family is a group of plants widely used empirically as traditional medicine to help control diabetes mellitus (DM) and has been supported by various experimental studies. This review aims to assess the types of Malvaceae family plants that have potential as antidiabetics and to summarize scientific evidence related to their pharmacological activity and the active compounds involved. The method used was a narrative review through a literature search in Google Scholar and PubMed for full-text articles published during 2011–2026. The included articles consisted of in vitro and in vivo studies discussing the antidiabetic or antihyperglycemic activity of Malvaceae family plants, while duplicate articles, review articles, proceedings, and irrelevant publications were excluded. Based on the selection process, several articles met the criteria for descriptive analysis. The results showed that several Malvaceae family plants have antidiabetic potential, including hibiscus (Hibiscus rosa-sinensis), roselle (Hibiscus sabdariffa), okra (Abelmoschus esculentus), durian (Durio zibethinus), sidaguri (Sida cordifolia), kapas hantu (Abroma augusta), biruan (Grewia asiatica), kapuk (Ceiba pentandra), kembang sore (Abutilon indicum), and pulutan (Urena lobata), all reported to have blood glucose-lowering effects. This activity is related to secondary metabolites such as flavonoids, alkaloids, tannins, saponins, and phenolic compounds, which act through antioxidant mechanisms, increased insulin sensitivity, inhibition of α-amylase and α-glucosidase enzymes, and protection of pancreatic β cells. Based on these findings, Malvaceae family plants have the potential to be developed as sources of natural medicine candidates and supportive therapies in the management of diabetes mellitus.